Habilidades sociais e satisfação conjugal de mulheres em situação de violência perpetrada por parceiro íntimo - Cardoso, Bruno Luiz Avelino (2017)
The development of satisfactory interpersonal relationships has contributed decisively to a quality of life and psychological health of the people. On the other hand, a difficulty in maintaining relationships in a healthy way and using conflict resolution strategies can lead to losses in the affective relationships between family members, spouses and partners and / or boyfriends contributing to violence against women by an intimate partner. It is understood that a satisfying conjugal relationship demands social skills like exchange of affection, search for approximation, problem solving, and others. These aspects highlight the relevance of investigations regardin the characterization of repertoire of social skills, marital satisfaction and the relationship between these variables in women in situation of intimate partner violence.. This study aims to analyze a relationship between social skills and marital satisfaction of women in situations of intimate partner violence. This study aims to analyse the relationship between social skills and marital satisfaction of women in situations of intimate partner violence. To achieve this goal, 23 women, from na institution specializing in the care of women in situation of violence, responded to three instruments: Questionnaire on Degree and Form of Violence by a woman practiced by intimate partner, Marital Satisfaction Scale, and Inventory of Marital Social Skills. The results showed that the highest levels of violence reported by the women interviewed were of a psychological nature and the level of marital satisfaction is inversely proportional to the situations of intimate partner violence. In addition, women in situations of intimate partner violence self-rated with a total deficit of marital social skills, especially in "expressiveness/empathy", "self-assertiveness " and "proactive self-control" classes, showing difficulties in expressing feelings and thoughts in the marital relationship, guaranteeing their rights to individuality in the relationship, demonstrate empathic understanding, recognize the signs of physiological change in oneself and in the other. The data obtained through correlation pointed out that as general marital social skills and the proactive self-control class was negatively related to the increase in marital dissatisfaction. It was also observed that the more assertive conversational skills the greater the marital dissatisfaction (and with the aspects of the conjugal interaction). It's shown that assertive self-assertion and proactive self-control are also negatively related to an occurrence of violence (general and sexual). Thus, the importance of social skills training for this population and the understanding of the nature of assertive responses in the sociocultural context is noted. The use of social skills contrasts with violent relationships. In this sense, this study contributes to the understanding of the classes of marital social skills that can be targeted for intervention among the population of women in situations of intimate partner violence. The training of these skills, not only for a woman, but for the couple, can be an essential tool for the development of socially competent relationships, based on respect for each other and expansion of marital satisfaction.